2017
DOI: 10.1158/1078-0432.ccr-16-1298
|View full text |Cite
|
Sign up to set email alerts
|

Gas6/AXL Signaling Regulates Self-Renewal of Chronic Myelogenous Leukemia Stem Cells by Stabilizing β-Catenin

Abstract: Quiescent leukemia stem cells (LSC) are important resources of resistance and relapse in chronic myelogenous leukemia (CML). Thus, strategies eradicating CML LSCs are required for cure. In this study, we discovered that AXL tyrosine kinase was selectively overexpressed in primary CML CD34 cells. However, the role of AXL and its ligand Gas6 secreted by stromal cells in the regulation of self-renewal capacity of LSCs has not been well investigated. The function of CML CD34 cells was evaluated by flow cytometer, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…The AXL‐dependent epirubicin resistance mediated by c‐MYC is likely achieved through regulation of the stemness of a subset of self‐renewing EAC stem cells. Our findings are consistent with the recent report showing that Gas6/AXL signaling stabilizes β‐catenin protein in an AKT‐dependent mechanism, thereby regulating self‐renewal of drug‐resistant leukemia stem cells (Jin et al ., ). We confirmed that pharmacologic inhibition of AXL by R428 is sufficient to down‐regulate c‐MYC expression and overcome epirubicin resistance in EAC cells.…”
Section: Discussionmentioning
confidence: 97%
“…The AXL‐dependent epirubicin resistance mediated by c‐MYC is likely achieved through regulation of the stemness of a subset of self‐renewing EAC stem cells. Our findings are consistent with the recent report showing that Gas6/AXL signaling stabilizes β‐catenin protein in an AKT‐dependent mechanism, thereby regulating self‐renewal of drug‐resistant leukemia stem cells (Jin et al ., ). We confirmed that pharmacologic inhibition of AXL by R428 is sufficient to down‐regulate c‐MYC expression and overcome epirubicin resistance in EAC cells.…”
Section: Discussionmentioning
confidence: 97%
“…Axl, a member of the receptor tyrosine kinase family and a prognostic marker in AML, induces the expression of its ligand Gas6 (growth arrest-specific gene 6) from the BMM and increases the proliferation of leukemic cells (Janning et al, 2015). The same axis has been reported to regulate the self-renewal of CML cells (Jin et al, 2017). Additionally, secreted vesicles, called exosomes or microvesicles, are emerging factors in the evolution and progression of different cancer types, including leukemia (Krause and Scadden, 2015) (see poster and Box 2).…”
Section: Cytokines Chemokines and Secreted Vesicles In The Extracellmentioning
confidence: 98%
“…Peripheral blood (PB) or bone marrow (BM) samples were obtained from patients with CML (Supplementary Table S1) and from healthy adult donors in the First Affiliated Hospital of Jinan University, The First Affiliated Hospital of Sun Yat-sen University, Sun Yat-sen Memorial Hospital, and Guangdong Provincial People's Hospital after informed consent according to the institutional guidelines and the Declaration of Helsinki principles. The primary human CD34 þ cells were sorted by using a MACS bead kit (Miltenyi Biotec) as described previously (8,14,17).…”
Section: Cell Lines and Primary Leukemia Cellsmentioning
confidence: 99%
“…The maintenance of LSCs is independent of BCR-ABL kinase activity (11), but regulated by multiple signaling pathways including the developmental signaling pathways (e.g., Wnt/b-catenin, Notch, Hedgehog), epigenetic regulators (e.g., SIRT1, PRMT5, EZH2), transcriptional factors (e.g., p53, NF-kB, FOXM1), cell metabolism regulators (e.g., Slc15A2, Alox5), and other cell regulators (e.g., PPARg, Gas6/AXL, IL1RAP, PTEN; refs. [12][13][14][15][16][17][18][19][20]. However, the signaling pathways that are responsible for LSC maintenance remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%